Age as a Predictor of Time to Response for Patients Undergoing Medical Management of Endometrial Cancer - Weirich, M Larissa; Larkins, Carolyn R; Craig, Wendy Y; Meserve, Emily; Febbraro, Terri; Lachance, Jason; Bradford, Leslie S (Clinical Journal of Obstetrics and Gynecology, 2023)
Objective: To explore the pathologic response rate to primary progesterone treatment in patients with Endometrial Intraepithelial Neoplasia (EIN) and early-stage endometrioid-type Endometrial Adenocarcinoma (EAC). Methods: Retrospective chart data were collected for patients with either EIN or EAC receiving primary progesterone treatment between 2015 and 2022. The presence of complete or partial response, time to response, and other demographic and treatment factors were recorded to determine independent predictors of response to progestin treatment. Results: In total, 112 women who were diagnosed with EIN or EAC were treated with upfront progestin therapy, of whom 79 had sufficient follow-up to assess response. Fifty patients (63%) responded, of whom 10 (20%) ultimately relapsed. Response was more robust among patients with EIN (79%, n = 33) compared with patients who had cancer (46%, n = 17). The median time to respond was 5.8 months overall. Diagnosis of EIN, younger age at diagnosis, and any pathologic evidence of progesterone effect were all predictors of treatment response. Younger patients had a significantly shorter time to partial or complete response with a median time to response of 5.9 months in patients ≤ 45 and 13.8 months in patients > 45. Conclusion: Our study demonstrated a lower overall response rate (63%) than reported in previous studies, especially for patients with cancer (46%). Younger patients had a significantly shorter time to respond than older patients. Pathologic progesterone effect observed at any time during treatment was a significant predictor of treatment response regardless of diagnosis and could serve as an early predictor of response to therapy.